The effect of NHT Google sites on critical thinking and motivational learning on stoichiometry material - Tasya Noor Nabila; Nurfina Aznam (Indonesian Journal of Educational Development (IJED), 2026)
Many students exhibit low levels of critical thinking and motivation for learning, indicating the need for innovative instructional approaches. This study aims to examine the impact of Numbered Heads Together (NHT) learning using Google Sites on students' critical thinking and motivation to learn. This research was conducted in two high schools in Yogyakarta. This study employed a quantitative quasi-experimental design, involving students from 11th-grade science classes. The experimental group learned NHT on Google Sites, whereas the control group received instruction using a scientific approach. The sampling technique uses a cluster random sampling. The research instrument uses a test and a questionnaire, and data are collected through pretest and posttest measures. Furthermore, the data were analyzed using MANOVA. The results from hypothesis tests showed significant differences in students' critical thinking and motivational learning, both simultaneously and separately, between students who were given NHT-Google Sites and those who were given a scientific approach, with a simultaneous effective contribution of 31.4%, which is categorized as large. and separately, 26,2% for critical thinking skills and 14,8% for student learning motivation, each of which was in a large category. Overall, students' critical thinking and motivation to learn in NHT using Google Sites were higher than those of students who received instruction using a scientific approach. These findings suggest that the Numbered Heads Together learning model, when implemented with Google Sites, can be an effective instructional strategy for enhancing students' critical thinking skills and motivation to learn.